2015
DOI: 10.15287/afr.2015.304
|View full text |Cite
|
Sign up to set email alerts
|

Seed germination characteristics of Phillyrea angustifolia L. and P. latifolia L. (Oleaceae), two Mediterranean shrub species having lignified endocarp

Abstract: Abstract. The aim of this study was to determine the germination characteristics of Phillyrea angustifolia L. and P. latifolia L. seeds in order to develop an optimized propagation protocol for Phillyrea species. Seeds of P. angustifolia and P. latifolia were collected from wild plants growing in Cáceres province (CW Spain) and Andalucía (S Spain), respectively. Percentage of water uptake for P. latifolia seeds was calculated. Seeds with and without endocarp were germinated at different constant and alternatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
15
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 29 publications
5
15
2
Order By: Relevance
“…This clearly shows a certain positive effect of GA 3 on the germination of P. latifolia seeds, which is not present in all other pre-treatments (figure 4). Similar results (21 %) of the effect of GA 3 at 1,000 mg L -1 on the germination are reported by Mira et al (2015). The positive effect of high GA 3 concentrations on seeds germination is reported in studies for other forest species such as the Arbutus unedo (Smiris et al 2006).…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…This clearly shows a certain positive effect of GA 3 on the germination of P. latifolia seeds, which is not present in all other pre-treatments (figure 4). Similar results (21 %) of the effect of GA 3 at 1,000 mg L -1 on the germination are reported by Mira et al (2015). The positive effect of high GA 3 concentrations on seeds germination is reported in studies for other forest species such as the Arbutus unedo (Smiris et al 2006).…”
Section: Discussionsupporting
confidence: 83%
“…Mira et al (2015) found that cold stratification at 5 °C had a negative effect on seed germination of P. angustifolia and P. latifolia seeds in Spain, probably inducing secondary dormancy. In contrast, 30.1 % germination after two months of cold stratification at 3-4 °C for P. latifolia seeds is reported by the Aygün et al (2011), which directly contradicts our results.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations